2016
DOI: 10.17957/tpmj/16.3583
|View full text |Cite
|
Sign up to set email alerts
|

POSTMENOPAUSAL UTERINE BLEEDING; CORRELATION OF THE FINDINGS OF TRANSVAGINAL ULTRASONOGRAPHY & ENDOMETRIAL SAMPLING IN PATIENT

Abstract: ABSTRACT… Objectives: To find out the significance of the transvaginal sonography (TVS) in postmenopausal women (PMW) with postmenopausal bleeding (PMB) and compare it with the histopathological diagnosis at curettage, so that unnecessary operations could be avoided. Study Design: Descriptive study. Setting: Radiological Department for TVS and H/P at the Department of Gynecology & Obstetrics (Gynae: Unit IV) at Liaquat University Medical, Health Sciences Hospital Jamshoro and Hyderabad. Period: September 2010 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…20 Another study done by Memon et al on 112 postmenopausal women with uterine bleeding showed postmenopausal atrophic endometrium in 64 (57.14%) patients, endometrial polyp in 5 (4.16%) patients, endometrial hyperplasia in 27 (24.10%) patients, endometrial carcinoma in 8 (7.14%) patients, pyometra in four (3.57%) patients and fibroid uterus in four (3.57%) patients. 21 While in the study done by Moradan et al, 22 the reported results on transvaginal sonography were atrophy in 30 (50%), hyperplasia in 13 (21.66%), endometrial polyp in 16 (26.66%) and carcinoma in one (1.6%). Another study conducted by Sadoon et al 24 on 142 patients reported that the incidence of endometrial pathology was found to be of 23.9% and only 5% for endometrial carcinoma, also they found that benign endometrial pathologies are the most common cause of postmenopausal bleeding, this in agreement with our study.…”
Section: Discussionmentioning
confidence: 90%
“…20 Another study done by Memon et al on 112 postmenopausal women with uterine bleeding showed postmenopausal atrophic endometrium in 64 (57.14%) patients, endometrial polyp in 5 (4.16%) patients, endometrial hyperplasia in 27 (24.10%) patients, endometrial carcinoma in 8 (7.14%) patients, pyometra in four (3.57%) patients and fibroid uterus in four (3.57%) patients. 21 While in the study done by Moradan et al, 22 the reported results on transvaginal sonography were atrophy in 30 (50%), hyperplasia in 13 (21.66%), endometrial polyp in 16 (26.66%) and carcinoma in one (1.6%). Another study conducted by Sadoon et al 24 on 142 patients reported that the incidence of endometrial pathology was found to be of 23.9% and only 5% for endometrial carcinoma, also they found that benign endometrial pathologies are the most common cause of postmenopausal bleeding, this in agreement with our study.…”
Section: Discussionmentioning
confidence: 90%